Lidocaine Promoted Ferroptosis by Targeting miR-382-5p /SLC7A11 Axis in Ovarian and Breast Cancer - Dan Sun; Ying-Chun Li; Xiao-Yu Zhang (Frontiers Media S.A., 2021)
Ovarian and breast cancer are prevalent female malignancies with increasing occurrence incidence and metastasis, significantly affecting the health and life quality of women globally. Anesthetic lidocaine has presented anti-tumor activities in the experimental conditions. However, the effect of lidocaine on ovarian and breast cancer remains elusive. We identified the important function of lidocaine in enhancing ferroptosis and repressing progression of ovarian and breast cancer. Our data showed that lidocaine further repressed erastin-inhibited ovarian and breast cancer cell viabilities. The treatment of lidocaine induced accumulation of Fe2+, iron and lipid reactive oxygen species (ROS) in ovarian and breast cancer cells. The ovarian and breast cancer cell proliferation was suppressed while cell apoptosis was induced by lidocaine in vitro. Lidocaine attenuated invasion and migration of ovarian and breast cancer cells as well. Regarding the mechanism, we found that lidocaine downregulated solute carrier family 7 member 11 (SLC7A11) expression by enhancing microRNA-382-5p (miR-382-5p) in the cells. The inhibition of miR-382-5p blocked lidocaine-induced ferroptosis of ovarian and breast cancer cells. MiR-382-5p/SLC7A11 axis was involved in lidocaine-mediated inhibition of ovarian and breast cancer cell proliferation in vitro. The miR-382-5p expression was down-regulated but SLC7A11 expression was up-regulated in clinical ovarian and breast cancer samples. Furthermore, the treatment of lidocaine repressed tumor growth of ovarian cancer cells in vivo, in which the miR-382-5p expression was increased while SLC7A11 expression was decreased. Consequently, we concluded that the lidocaine promoted ferroptosis by miR-382-5p/SLC7A11 axis in ovarian and breast cancer cells. The clinical value of lidocaine in the treatment of ovarian and breast cancer deserves to be proved in detail.